Eurasian Encounters : Museums, Missions, Modernities - Kikuchi, Yoshiyuki; Stolte, Carolien (Book collections on Project MUSE., 2017)
The essays in this volume explore crucial intellectual and cultural exchanges between Asia and Europe in the first half of the twentieth century. Examining the increased mobility of people and information, scientific advances, global crises, and the unravelling of empires, Eurasian Encounters demonstrates that this time period saw an unprecedented increase in a transnational flow of politically and socially influential ideas. Together, the contributors show how the two ends of Eurasia interacted in artistic, academic, and religious spheres using new international and cosmopolitan approaches.--